Valvular aspects from echocardiography in rheumatic heart disease - Noverike, Nikhen; Anna Fuji Rahimah; Yogibuana, Valerinna; Karolina, Wella (Heart Science Journal, 2025)
Rheumatic Heart Disease is a result of an autoimmune response to group A streptococcal infection and is globally impacted and prevalent in low- and middle-income countries, especially among children and young adults. It primarily affects the heart valves, leading to damage and dysfunction. The progression of RHD can vary, with some individuals experiencing mild symptoms while others may develop severe valve damage leading to heart failure. Echocardiography plays a crucial role in the diagnosis and monitoring of RHD, as it allows to visualize and assess the structural and functional abnormalities of the heart valves. Early detection through echocardiography screening is essential for timely intervention and management of RHD. It provides valuable information about the severity of valve damage and helps determine the most appropriate treatment approach, whether it involves medication or surgical intervention. The ability of echocardiography to provide information about volumes, flows, and pressures, and to acquire quantitative hemodynamic data, highlights its importance in the assessment of patients with RHD. In conclusion, echocardiography has revolutionized the way we diagnose, monitor, and manage rheumatic heart disease, and its importance in the medical field cannot be overstated. The continued integration of echocardiography into clinical practice will undoubtedly lead to improved outcomes for patients with RHD.